Review of the Camponotus samius complex (Hymenoptera: Formicidae) in the Turano-Balkan region, with the description of a new species from Iran - Salata, Sebastian; Khalili-Moghadam, Arsalan; Borowiec, Lech (Zootaxa, 2020)
Here we define the Camponotus samius complex, a distinct subunit within the compressus-sylvaticus group, and revise the species known from the Turano-Balkan region (the Balkans, Middle East, Anatolia, Caucasus, Iran and W Turkestan). We confirm the presence of six species of the complex from the Turano-Balkan region, and we provide diagnoses and a key. Additionally, based on new material from the Chaharmahal va Bakhtiari Province of Iran, we describe Camponotus bakhtiariensis sp. nov.—a new member of the samius complex.